EKSEKUSI PENGELOLAAN ROYALTI BERBASIS BLOCKCHAIN DENGAN FITUR SMART CONTRACT DALAM EKOSISTEM INDUSTRI DIGITAL - Silalahi, Andreas Parasian; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The writing of the paper aims to study the blockchain technology in terms of royalty distribution, which offers an efficient, transparent, and secure solution. The major issue of this study is about how the blockchain-based royalty execution mechanisms can be aligned with Copyright Law. This research employs a normative methodology based on the primary legal sources, namely legal norms from regulations and jurisprudence, secondary legal sources, namely thoughts related to the study drawn from legal facts, doctrines, books, journals, the internet, and other sources, as well as tertiary legal sources that provide additional information or guidelines derived from primary as well as secondary legal sources. The results of current study imply hat the technology can be implemented without conflicting with the existing regulations and provide a stronger copyright protection and a fairer royalty distribution. Challenges faced include technology adoption and regulatory adjustments in the future.Keywords: Blockchain, Smart Contract, Royalty.